The Influence of Product Quality, Service Quality and Price on Repurchase Interest with Consumer Satisfaction as a Mediating Variable: Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Minat Beli Ulang Dengan Kepuasan Konsumen Sebagai Variabel Mediasi - Selvi Harmiyanti; Fitria Ridha Ningsih (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the effect of product quality, service quality and price on repurchase intention mediated by consumer satisfaction towards mie gacoan in Padang city. Using a quantitative approach, data were collected from 128 respondents who live in Padang city and have bought mie gacoan more than 2 times with an age range of 17 - 30 years using an online questionnaire. data were analyzed using IBM SPSS Statistics. the results of this study indicate that product quality and service quality have a significant effect on consumer satisfaction. price does not have a significant effect on consumer satisfaction. service quality and price have a significant effect on repurchase intention, while product quality does not have a significant effect on consumer satisfaction. consumer satisfaction has a significant effect mediating service quality and price on repurchase intention. in addition, consumer satisfaction does not have a significant effect in mediating product quality on repurchase intention. this study expects the need for other strategies to be able to increase repurchase intention towards mie gacoan restaurants in Padang city.